Kajian Etnomatika: Mengungkap Penggunaan Alat Ukur Beras di Suatu Wilayah di Indramayu - Eyus Sudihartinih (Universitas PGRI Adi Buana Surabaya, 2023)
Ethnomathematics is important because of the need to integrate real cultural values in learning mathematics. West Java is one of the provinces in Indonesia which has a variety of ethnomathematics, one of which is Indramayu. Some of the people of Indramayu still use the traditional rice measurement tool so that it can become an ethnomathematics study. Therefore, the aim of this study is to describe the results of an ethnomathematics study on the use of rice measuring instruments in the communities of several Indramayu regions. This research method is ethnography with five female and one male participants. Data collection was carried out by triangulation, namely documentation, interviews, field notes, and observations. The result of this research is that there is ethnomathematics in the use of traditional rice measurement tools in the Indramayu community. So that further research is needed to apply ethnomathematics to learning mathematics on the topic of introducing volume units, mass units, and fractional numbers in the area.